Allocation algorithm for athletes group to form tactical tasks in game team sports using the methods of multivariate analysis (illustrated women Ukrainian team basketball with hearing impairments) - Kozina, Z. L.; Sobko, I. N.; Kolomiec, N. A.; Jagiello, W.; Jagiello, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: develop and prove experimentally allocation algorithm athletes in groups to form a tactical tasks in team sports game using methods of multivariate analysis.